Integrated Science Learning Using Scientific Approach in Junior High Schools in Semarang Regency - Debora Natalia Sudjito; Natalia R. Keliat; Susanti P. Hastuti (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The scientific approach is strongly suggested to be used in implementing “Curriculum of 2013” (K13) by Department of Education. This study aimed to identify whether integrated science learning was implemented in Junior High Schools in the Semarang Regency, Indonesia used a scientific approach, how it was implemented, and what problems that emerged in it. This research was conducted in 13 Junior High Schools in Semarang Regency, Central Java Province that implemented K13 during the odd semester in 2016/2017 school year by interviewing the science teachers in each school to determine how scientific approach was implemented in their schools. Based on the interview results analyzed using qualitative description methods, K13 was implemented, teachers used a scientific approach to teach science subject in their classes, and they integrated science materials in the curriculum. However, not all of the science materials were able to be integrated and taught using scientific approach because the teachers’ educational background is not from science education. Furthermore, the availability of the teachers and students books, the laboratory facilities, and funds were very limited. Many solutions such as using various learning models were done, but they were not be able to maximize the learning even though the students were active and enthusiastic in learning. Therefore, the teachers really need real supports to enhance their learning using scientific approach.Keywords: integrated science learning, scientific approach, curriculum of 2013, junior high school